Mercury release of amalgams with various silver contents after exposure to bleaching agent - Mahmoud (Journal of Dental Research, Dental Clinics, Dental Prospects, 2016)
Background. Since it is possible for carbamide peroxide (CP) bleaching agent to contact old amalgam restorations, the present in vitro study evaluated the amount of dissolved mercury released from amalgam restorations with various percent-ages of silver content subsequent to the use of 15% CP. Methods. Thirty ANA 2000 amalgam disks with 43.1% silver content and thirty ANA 70 amalgam disks with 69.3% silver content were prepared. In each group, 15 samples were randomly placed in glass tubes containing 15% CP (as experimental groups) and the remaining 15 samples were placed in buffered phosphate solution (as control groups) with the same 3-mL volume for 48 hours. Subsequently, the amount of mercury dissolved in each test tube was measured using Mercury Ana-lyzing System (Cold Vapor Atomic Absorption, MASLO, Shimadzu, Japan). Data was analyzed with two-way ANOVA and a post hoc Tukey test. (α = 0.05) Results. The amount of mercury released after exposure to CP was significantly higher than that released after exposure to buffered phosphate (P < 0.001). In addition, the amount of mercury released from dental amalgam with a silver content of 43% was significantly higher than that released from dental amalgam with a silver content of 69% (P < 0.001). Conclusion. The amount of mercury release is inversely proportional to the silver content of dental amalgam.